Effect of early dry season induced by the Three Gorges Dam on the soil microbial biomass and bacterial community structure in the Dongting Lake wetland. (June 2015) - Wu, Haipeng; Zeng, Guangming; Liang, Jie; Guo, Shenglian; Dai, Juan; Lu, Lunhui; Wei, Zhen; Xu, Piao; Li, Fei; Yuan, Yujie; He, Xiaoxiao
Highlights: Early dry-season is the key effect of Three Gorges Dam on downstream wetlands. Responses of soil microbe to dry-season early by 0, 20 and 40 days were examined. Soil microbial biomass had an increase as dry-season lead time extension. Diversity of soil bacterial of E20 (early by 20 days) was similar to that of E0. Diversity of soil bacterial of E40 (early by 40 days) was higher than that of E0. Abstract: In this study, we used the soil microbial biomass (SMB) and the bacterial community structure as indicators to determine the potential ecological responses of the Dongting Lake wetland (China) to the early dry season that has been induced by the Three Gorges Dam (TGD), the largest hydroelectric project in the world. We measured the soil properties, SMB and bacterial community structure for samples E0, E20 and E40 (for which the dry season arrived early by 0, 20 and 40 days, respectively). The results indicated a significant increase in SMB as the dry season occurred increasingly earlier. The microbial biomass carbon (MBC) was used as a representative for the SMB and increased for the samples in the following order: E0 < E20 < E40. The bacterial 16S rDNA gene copy number changed similarly to the MBC. Significant changes were also observed in the soil bacterial community structure. The bacterial community structure of E40 was more diverse than that of E20, which was similar to that of E0. The relationship between the bacterial community composition and the soil properties was evaluated by redundancy analysis (RDA). The results indicated that the lead time of the dry season was the controlling influence on the soil bacterial community structure.